PERAN DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN KAMPAR DALAM PENGEMBANGAN OBYEK WISATA DANAU BOKUOK DI DESA AURSATI KECAMATAN TAMBANG TAHUN 2010-2012 - M. Hafiz Al Gerry; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted in the village of Aursati District of Kampar Regency Mines. Based on the Kampar Regency Regulation No. 06 of 2008 concerning the organizational structure and working procedures Kampar District Local Government has the principal task of implementing regional government authority in the field of Tourism and culture. It is to know the role of the Department of Tourism and Culture Kampar district in the development of tourist attraction in the village of Lake Bokuok Aursati District of mine. This study used qualitative methods. Data collection techniques in this study were interviews and tracking documentation. Department of Tourism and Culture Kampar Regency has a strategic role in the effort to accelerate the development of an area, especially in the field of tourism. 7 In this study determined the informant is the Head of Tourism and Culture Kampar District, the Village Head and Head of Indigenous ninik Aursati Mamak Kenegerian Mine. Based on the research that the development of tourism development bokuok Lake has yet to be maximized, some contributing factor is the lack of budget priorities of the Government of Kampar district, the absence of village regulations on tourism, quality of human resources is still weak tourism actors. Thus the Department of Tourism and Culture should be an evaluation of existing service programs so that every potential that exists in the area can be maximized. So also with the village government and its Aursati ninik mamak Kenegerian Indigenous Mine also have to be more creative and cooperative in addressing any existing problems, especially concerning the cultural festival this Bokuok lake. Bokuok Lake Festival is a major attraction for tourists to visit the Lake Bokuok. Keywords: Roles, Tourism, Lake Bokuok Development, Tourism and Culture Department Kampar district.